(untitled) (PYC Nepal Journal of Management, 2012)
This study examines the investors’ behaviours on stock return. This study investigates the investors’ use of CAPM assumption which relates to homogeneous expectation concerned with the investor’s perception and human behaviour, and also affects investments in security market. The survey-based study concludes that Nepalese investors prefer a long position strategy and consider that price of the share is the deciding factor in security trading. Similarly, the study shows that a firm size effect exists in stock returns in Nepal.